Обрахунки жертв українсько-польського конфлікту на Любомльщині в українських і польських джерелах: спроба порівняння - Крамар, Юрій Вікторович; Kramar, Yurii V. (Східноєвропейський національний університет імені Лесі Українки, 2019)
The calculation of victims in the Ukrainian-Polish conflict in the period of the Second World War is one of the most complicated theme in the modern Ukrainian and Polish historiography. To carry out this accounts without access to all accessible archive materials, documentary confirmed evidence of witnesses of those events in the scales of all Volyn, East Galychyna, Chelm and Podlassie lands seem an extraordinary complicated thing now (though not hopeless). It is easier to do it on the example of concrete region and separate local places. The aim of this publication consists of following: firstly, in this case, on the basis of analyzing of different sources the author tries to set the number of victims in the Ukrainian-Polish conflict in the years 1943–1944 in Luboml region; secondly – to find out the factors that caused a discrepancy in the accounting of victims from the Ukrainian and Polish sides in the separately taken region. An acquaintance with the sources has a ground to talk about the fact that while counting Ukrainian and Polish victims in the time of conflict it doesn’t pay attention on a number of circumstances which caused ethnic and demographic transformations in the region during the whole period of the Second War (1939–1945). They made a noticeable influence on the motion of the Ukrainian and Polish population in the region.
Keywords: Волинь-43; Volyn-43